2016
DOI: 10.1007/s00464-016-5381-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic cholecystectomy versus conventional four-port laparoscopic cholecystectomy: a systematic review and meta-analysis

Abstract: Background Single-incision laparoscopic cholecystectomy (SILC) might maximize the advantages of laparoscopic cholecystectomy (LC) by reducing postoperative pain and improving cosmesis. However, the safety and feasibility of SILC has not yet been established. This study assesses safety, patient reported outcome measures and feasibility of SILC versus conventional LC. Methods Literature search for RCT's comparing SILC with conventional LC in gallstone-related disease was performed in PubMed and Embase. The conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 20 publications
4
69
0
2
Order By: Relevance
“…Several studies [14, 15] and one meta-analysis [16] have demonstrated that NSC has the advantage of eliciting both a reduced level of wound pain and a reduced need for postoperative analgesia in comparison to CLC. Other meta-analyses have also shown the advantages of SILC over CLC regarding postoperative pain [17-19]. Because no previous studies have compared postoperative pain between SILC and NSC, our results suggest that needlescopic approaches, including NSC, result in less postoperative pain because less damage is caused to the abdominal wall in comparison to both CLC and SILC.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies [14, 15] and one meta-analysis [16] have demonstrated that NSC has the advantage of eliciting both a reduced level of wound pain and a reduced need for postoperative analgesia in comparison to CLC. Other meta-analyses have also shown the advantages of SILC over CLC regarding postoperative pain [17-19]. Because no previous studies have compared postoperative pain between SILC and NSC, our results suggest that needlescopic approaches, including NSC, result in less postoperative pain because less damage is caused to the abdominal wall in comparison to both CLC and SILC.…”
Section: Discussionmentioning
confidence: 52%
“…The novelty of this study comes from the application of SILS to abdominal cerclage placement compared with the more commonly used MPLS technique. In SILS, a single transumbilical incision is closed to create a scarless cosmetic appearance . Findings from a prospective cohort study of postoperative pain in SILS and multiport surgery performed by our team showed a significant decrease in overall pain with SILS along with a decrease in overall use of pain medication.…”
Section: Demographic Perioperative and Pregnancy Outcomesmentioning
confidence: 86%
“…With recent advances in surgical instruments and techniques, the application of minimally invasive surgery has further expanded to smaller wounds. Single‐incision laparoscopic cholecystectomy (SILC) has shown comparable operative outcomes, with nearly scarless cosmetic results, to those of conventional three‐incision laparoscopic cholecystectomy (C‐TILC) . Despite the incremental application of SILC in clinical practice, it has been shown to be more technically difficult than C‐TILC.…”
Section: Introductionmentioning
confidence: 99%
“…Single-incision laparoscopic cholecystectomy (SILC) has shown comparable operative outcomes, with nearly scarless cosmetic results, to those of conventional three-incision laparoscopic cholecystectomy (C-TILC). [1][2][3] Despite the incremental application of SILC in clinical practice, it has been shown to be more technically difficult than C-TILC. In SILC, the instruments inserted through the small incision tend to collide, and the narrow area of movement leads to physical disturbance between the surgeon and the camera assistant.…”
Section: Introductionmentioning
confidence: 99%